Tricarboxylic Acid Cycle Regulation of Metabolic Program, Redox System, and Epigenetic Remodeling for Bone Health and Disease - Wei-Shiung Lian; Re-Wen Wu; Yu-Han Lin; Yu-Shan Chen; Holger Jahr; Feng-Sheng Wang (MDPI AG, 2024)
Imbalanced osteogenic cell-mediated bone gain and osteoclastic remodeling accelerates the development of osteoporosis, which is the leading risk factor of disability in the elderly. Harmonizing the metabolic actions of bone-making cells and bone resorbing cells to the mineralized matrix network is required to maintain bone mass homeostasis. The tricarboxylic acid (TCA) cycle in mitochondria is a crucial process for cellular energy production and redox homeostasis. The canonical actions of TCA cycle enzymes and intermediates are indispensable in oxidative phosphorylation and adenosine triphosphate (ATP) biosynthesis for osteogenic differentiation and osteoclast formation. Knockout mouse models identify these enzymes' roles in bone mass and microarchitecture. In the noncanonical processes, the metabolites as a co-factor or a substrate involve epigenetic modification, including histone acetyltransferases, DNA demethylases, RNA m6A demethylases, and histone demethylases, which affect genomic stability or chromatin accessibility for cell metabolism and bone formation and resorption. The genetic manipulation of these epigenetic regulators or TCA cycle intermediate supplementation compromises age, estrogen deficiency, or inflammation-induced bone mass loss and microstructure deterioration. This review sheds light on the metabolic functions of the TCA cycle in terms of bone integrity and highlights the crosstalk of the TCA cycle and redox and epigenetic pathways in skeletal tissue metabolism and the intermediates as treatment options for delaying osteoporosis.